Online medical education for international medical students of China; a necessity or a convenience? - Fatima, Maurish; Murad, Muhammad Wahaj; Cheema, Huzaifa Ahmad (Journal of the Pakistan Medical Association, 2023)
Madam, The primary aim of this letter is to start a conversation around online education for international medical students currently enrolled in medical schools in China. Where Coronavirus (COVID-19) pandemic had significant negative economic impacts, it also led to the emergency imposition of several healthcare policies, including lockdown measures, social distancing and optimum hygienic measures. The closure of medical schools, the suspension of flights, and the disruption in face-to-face learning trajectories have been challenging for international medical students across the globe. This has led to transition from usual face-to-face to current online education system. Several studies have concluded online education to be an effective mode of teaching for undergraduate medical students(1,2). A similar strategy was adopted by several medical universities in China to accommodate the international medical students where, 68,000 international medical students are currently studying in about 100 medical universities (3). Despite, relaxation in COVID-19 restrictions and lifting of the travel ban, online teaching remains to be the primary learning modality for international medical students studying in China. A recently published study by Li et al. surveyed 230 international medical students receiving online education in a Chinese university to assess the online education’s quality and student satisfaction (4). The results showed 63.5% of students expressing dissatisfaction with online learning among whom 72% were from clinical years. Though E-learning is accepted as a more convenient mode of education, it is limited in promoting practical competence. Clinical exposure and in-person interaction with patients have an integral role in the medical curriculum. It is still argued whether tele-rotations or online modules can substitute for these core competencies (5). Many countries across the globe have resumed on-campus classes, and even the local students in China are returning to their respective colleges. This evokes further uncertainty among international medical students regarding their career and learning outcomes. Factors such as poor internet connection and pandemic induced financial burdens have been found to have negatively influenced the online-learning experience. (4). There are also serious concerns regarding the quality of education and the online assessment methods employed by various medical schools in China for international medical graduates. One proposed solution to all this could be that medical schools in China should collaborate with overseas medical schools and hospitals, particularly those located in the international medical students’ countries of origin. This can provide alternative experiences locally for the experimental and clinical practice they are missing.